Adaptive deep brain stimulation (aDBS) for Parkinson's disease. Issue 3 (March 2016) - Priori, A.; Arlotti, M.; Rosa, M.; Marceglia, S.
Abstract : Adaptive deep brain stimulation (aDBS) controlled by local field potentials (LFPs) can improve the clinical benefits induced by conventional DBS (cDBS) in Parkinson's disease (PD). Data obtained in PD patients tested for minutes confirm the superiority of aDBS over cDBS. Testing adaptive approaches for longer time might have however inherent risks. We designed a randomized, double-blind, cross-over clinical trial to compare the amount of charge delivered, the safety and tolerability of 2 h aDBS versus 2 h cDBS using an external dual (cDBS or aDBS) mode portable device controlled by LFPs. Here we present the preliminary data on 7 patients with PD. Both aDBS and cDBS were administered for 2 h consecutively, during which the patient was assessed every 30 min, by a blinded investigator. Over the two hours of stimulation there were no treatment related adverse events (severe, moderate and mild) both during aDBS and cDBS. The patients exhibited a significant reduction of dyskinesias ( p  < 0.05) during aDBS compared to cDBS. The TEED during aDBS was 70% less than cDBS ( t -test, p  < 0.03). Preliminary data showed that aDBS is safe and well tolerated in PD patients and decreases the amount of TEED, thus obtaining a reduction of side effects.